On Equilibrium Pricing as Convex Optimization (Journal of Computational Mathematics, 2019)
We study competitive economy equilibrium computation. We show that, for the first time, the equilibrium sets of the following two markets: 1. A mixed Fisher and Arrow-Debreu market with homogeneous and log-concave utility functions; 2. The Fisher and Arrow-Debreu markets with several classes of concave non-homogeneous utility functions; are convex or log-convex. Furthermore, an equilibrium can be computed as convex optimization by an interior-point algorithm in polynomial time.
Keywords: Convex optimization; Competitive economy equilibrium; Non-homogeneous utility.